2022
DOI: 10.1093/eep/dvac002
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal acetaminophen use and acetaminophen metabolites with DNA methylation of newborns: analysis of two consecutive generations of the Isle of Wight birth cohort

Abstract: Background Acetaminophen is used by nearly two thirds of pregnant women. Although considered safe, studies have demonstrated associations of prenatal acetaminophen use and adverse health outcomes in offspring. Since DNA methylation (DNAm) at birth may act as an early indicator of later health, assessments on whether DNAm of newborns is associated with gestational acetaminophen use or its metabolites are needed. Methods Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, we found that acetaminophen intake was linked to the depressed serum of H3K4me3 changes during the acute peri-operative period. Some data suggest an effect of acetaminophen on DNA methylation [ 31 , 67 , 68 ]. DNA methylation affects histone modification.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that acetaminophen intake was linked to the depressed serum of H3K4me3 changes during the acute peri-operative period. Some data suggest an effect of acetaminophen on DNA methylation [ 31 , 67 , 68 ]. DNA methylation affects histone modification.…”
Section: Discussionmentioning
confidence: 99%
“…However, invasive testing of the foetal compartment in human is rarely indicated, which makes data on safety during pregnancy for most substances scant. Thus, most pharmacoepigenetic studies address associations of DNAm differences in cord blood or placenta from neonates delivered at term exposed to the maternal medication during pregnancy, which is also the case for paracetamol (82)(83)(84). We have previously published a study of cord blood samples from the Norwegian Mother, Father and Child cohort (MoBa), where we found differentially methylated genes in cord blood from children with ADHD exposed to long-term maternal paracetamol use (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, invasive testing of the fetal compartment in human is rarely indicated, which makes data on safety during pregnancy for most substances scant. Thus, most pharmacoepigenetic studies address associations of DNAm differences in cord blood or placenta from neonates delivered at term exposed to the maternal medication during pregnancy, which is also the case for paracetamol [83][84][85] .…”
Section: Discussionmentioning
confidence: 99%
“…Maternal blood samples were collected at the child's birth (predelivery) and were analyzed to measure metabolites, nutrients, and toxins (MNTs) using a data‐independent untargeted approach based on high‐resolution mass spectrometry coupled to varied sample introduction strategies (reversed‐phase liquid chromatography, hydrophilic interaction liquid chromatography, and flow‐injection analysis). Such an approached enabled a blind molecular profiling that does not require a priori knowledge of compound identities and is suitable for detecting a wide range of substances derived from environment, food, gut microbiome, and endogenous exposures 18,19 . Fucoxanthinol 3‐arachidate (nlp16.65_955.6949m_z) was measured using negative‐ion LC/high resolution MS on a Waters Xevo G2‐XS QTof mass spectrometer as its formate adduct ([M + formate] − ) as a continuous variable generated by the Progenesis QI software.…”
Section: Methodsmentioning
confidence: 99%
“…Such an approached enabled a blind molecular profiling that does not require a priori knowledge of compound identities and is suitable for detecting a wide range of substances derived from environment, food, gut microbiome, and endogenous exposures. 18,19 Fucoxanthinol 3-arachidate (nlp16.65_955.6949m_z) was measured using negative-ion LC/high resolution MS on a Waters Xevo G2-XS QTof mass spectrometer as its formate adduct ([M + formate] − ) as a continuous variable generated by the Progenesis QI software.…”
Section: Fucoxanthinol 3-arachidate Measurementmentioning
confidence: 99%